Water-smart circular economy : Conceptualisation, transitional policy instruments and stakeholder perception - Salminen, Jani; Määttä, Kalle; Haimi, Henri; Maidell, Marjo; Karjalainen, Anna; Noro, Kirsi; Koskiaho, Jari; Tikkanen, Sarianne; Pohjola, Johanna (Elsevier, 2022)
The Circular Economy (CE) is a concept that has gained considerable global attention during the past decade amongst private and public sector actors, politicians and policymakers, citizens and media, and scientific communities. Water and water-related ecosystems, despite their vital role in practically all human activities, have been largely missing from conceptualisations and scientific definitions of the CE. Therefore, this paper presents a definition and concept for a water-smart CE that incorporates water and water-related ecosystems. A water-smart CE would (i) reduce losses of water, energy and valuable substances, (ii) improve water efficiency and productivity, (iii) reuse treated wastewater, and (iv) better protect and lessen pressure upon water-related (both aquatic and groundwater) ecosystems. The paper also touches upon the potential risks of the CE to water-related ecosystems. Policy instruments that could be used to promote a transition towards a water-smart CE in Finland – the setting of the present study – and beyond were also sought. Additionally, actors who provide and/or use water-smart CE solutions were interviewed to shed light on their perceptions about the drivers of, barriers to and potential policy instruments for promoting a transition towards a water-smart CE. Based on the analyses of policy instruments and stakeholder interviews, a mixed use of economic, regulatory and informative instruments is suggested to support the desired transition towards a water-smart CE in Finland and elsewhere.
Keywords: Economic instruments; Sustainability transitions; Water use; circular economy; recycling; fi=Talousoikeus|en=Business Law|